Trust and political orientations - Freire, João (2011)
This paper discuss the rebirth of trust studies in recent years, especially in the field of political attitudes and opinions. The case study presented try to explore the relationship between electoral behaviour and political orientations, regarding the people's views about the role of state, market and 'third sector' and application of law or social self-regulation. We found prevailing statists and liberal orientations, but also a 'concealed' group of Portuguese voters.